Emerging Roles of m7G-Cap Hypermethylation and Nuclear Cap-Binding Proteins in Bypassing Suppression of eIF4E-Dependent Translation - Kathleen Boris-Lawrie; Jessica Liebau; Abdullgadir Hayir; Xiao Heng (Viruses)
Translation regulation is essential to the survival of hosts. Most translation initiation falls under the control of the mTOR pathway, which regulates protein production from mono-methyl-guanosine (m7G) cap mRNAs. However, mTOR does not regulate all translation; hosts and viruses alike employ alternative pathways, protein factors, and internal ribosome entry sites to bypass mTOR. Trimethylguanosine (TMG)-caps arise from hypermethylation of pre-existing m7G-caps by the enzyme TGS1 and are modifications known for snoRNA, snRNA, and telomerase RNA. New findings originating from HIV-1 research reveal that TMG-caps are present on mRNA and license translation via an mTOR-independent pathway. Research has identified TMG-capping of selenoprotein mRNAs, junD, TGS1, DHX9, and retroviral transcripts. TMG-mediated translation may be a missing piece for understanding protein synthesis in cells with little mTOR activity, including HIV-infected resting T cells and nonproliferating cancer cells. Viruses display a nuanced interface with mTOR and have developed strategies that take advantage of the delicate interplay between these translation pathways. This review covers the current knowledge of the TMG-translation pathway. We discuss the intimate relationship between metabolism and translation and explore how this is exploited by HIV-1 in the context of CD4+ T cells. We postulate that co-opting both translation pathways provides a winning strategy for HIV-1 to dictate the sequential synthesis of its proteins and balance viral production with host cell survival.